2013
DOI: 10.1016/j.livsci.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of starch with acid detergent fibre and/or neutral detergent soluble fibre at two protein levels: Effects on ileal apparent digestibility and caecal environment of growing rabbits

Abstract: The effects of the composition of peri-weaning diets on apparent ileal digestibility of nutrients and caecal environment were studied in growing rabbits. Eight diets were formulated according to a 2x2x2 factorial design to increase acid detergent fibre ( ; P<0.001) and reduced caecal pH (-0.10; P<0.05). In the low NDSF diets, higher ADF increased DM content of caecal digesta to a lesser extent (+16 g kg Overall, the three dietary changes under study led to changes in the caecal environment which might be effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
4
15
1
1
Order By: Relevance
“…Consistently, fermentative activity estimated as the VFA concentration in caecal digesta was 26% higher in HSF than LSF diets. This effect of SF replacing starch has been also previously reported (Xiccato et al, 2011;Martínez-Vallespín et al, 2013;Trocino et al, 2013b;Soler, 2014;Ocasio-Vega et al, 2018), in accordance with caecal VFA concentration increasing linearly with dietary SF content (Trocino et al, 2013a). Higher VFA concentration in ileal digesta when SF replaced starch has been also reported (Ocasio-Vega et al, 2018).…”
Section: Soluble Fibre Replacing Starchsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistently, fermentative activity estimated as the VFA concentration in caecal digesta was 26% higher in HSF than LSF diets. This effect of SF replacing starch has been also previously reported (Xiccato et al, 2011;Martínez-Vallespín et al, 2013;Trocino et al, 2013b;Soler, 2014;Ocasio-Vega et al, 2018), in accordance with caecal VFA concentration increasing linearly with dietary SF content (Trocino et al, 2013a). Higher VFA concentration in ileal digesta when SF replaced starch has been also reported (Ocasio-Vega et al, 2018).…”
Section: Soluble Fibre Replacing Starchsupporting
confidence: 84%
“…Higher VFA concentration in ileal digesta when SF replaced starch has been also reported (Ocasio-Vega et al, 2018). The effect on the caecal fermentation profile is controversial, as depending on the studies no changes (Trocino et al, 2013b; current study), an increase of butyrate at the expense of acetate (Martínez-Vallespín et al, 2013;Soler, 2014), and the opposite (Xiccato et al, 2011;Ocasio-Vega et al, 2018) have been observed. The discrepancies are probably due to methodological differences between experiments or/and to concurrent dietary changes induced by increasing SF at the expense of starch, which varied greatly between experiments, particularly those affecting the origin of the dietary soluble and, particularly, insoluble fibre.…”
Section: Soluble Fibre Replacing Starchmentioning
confidence: 61%
“…The quantification of soluble fibre in the digesta is more complex than in the diet/ingredients because the ethanol used to precipitate soluble fibre (in TDF analysis) also precipitates partially the intestinal mucins leading to an overestimation of ileal TDF content (Abad et al, 2013;Montoya et al, 2015). This seems to be the reason why the ileal digestibility of soluble fibre and TDF showed very low or even negative values both in rabbits (Gidenne, 1992;Martínez-Vallespín et al, 2013) and pigs (Jørgensen et al, 1996;Wilfart et al, 2007). A simple correction of digesta TDF values by the mucin carbohydrate fraction retained in the TDF residue was proposed by Abad et al (2013) and its application is essential when determining ileal digestibility of soluble fibre or TDF (especially in diets with low TDF or soluble fibre content) due to the relatively high ileal mucin content.…”
Section: Methods For Estimating the Dietary Fibre Content Of Animal Feedsmentioning
confidence: 99%
“…Meeting these requirements as accurately as possible with an adequate balance in essential nutrients can furthermore impact positively animal health. The literature has shown that in growing rabbits, an excess of dietary protein can contribute to a high incidence of mucoid enteropathy [ 5 , 6 , 7 , 8 ]. There are other studies, however, where the relationship between dietary protein and health status in growing rabbits is unclear [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%